Propozycja bazy danych dla Dorzecza Odry = Database for Odra basin - conception proposition - Parzyński, Zenon (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Plenty of main points of the Conference are convergent with the INSPIRE directive, especially those connected with an environment protection. Institutions, departments and partnerships interoperability is essential for a realization of those aims. If Odra basin is taken into consideration, interoperability of Germany and Poland is needed. The paper presents a conception of a common database for a border regions. The database will be next included into Odra basin database.
Keywords: baza danych rejonów przygranicznych; ATKIS; TBD; baza danych Dorzecza Odry; Dyrektywa INSPIRE; border regions database; Odra basin database; INSPIRE Directive